Characteristics of Propagation From Meteorological Drought to Hydrological Drought in the Pearl River Basin. Issue 4 (18th February 2021) - Zhou, Zhaoqiang; Shi, Haiyun; Fu, Qiang; Ding, Yibo; Li, Tianxiao; Wang, Yao; Liu, Suning
Abstract: Drought events occur more frequently under recent climate change. Generally, meteorological drought is the fuse of hydrological drought; thus, it is important to understand the characteristics of meteorological drought and its propagation to hydrological drought for early warning. Taking the Pearl River Basin (PRB) in China as study area, this study adopted K‐means cluster analysis method to divide the PRB into subregions with similar precipitation characteristics. Then, standardized precipitation index and standardized runoff index were used to analyze the characteristics of meteorological drought and hydrological drought, respectively, and the maximum Pearson correlation coefficient was used to determine the drought propagation time (DPT) between these two types of drought. Moreover, the link between meteorological drought and hydrological drought was explored based on continuous wavelet transform and cross wavelet transform. The results revealed that: the PRB has experienced severe meteorological and hydrological droughts since early 2000s, and hydrological drought was more serious than meteorological drought in each of the five subregions in the PRB. The DPTs from meteorological drought to hydrological drought were mainly 2–6 months, and the periodic characteristics of meteorological drought were mainly responsible for those of hydrological drought. Precipitation and runoff could greatly affect the DPT, while the impacts of evapotranspiration and shallow soil moisture on the DPT were not significant. Furthermore, El‐Niño Southern Oscillation and Pacific Decadal Oscillation are important factors that affect the DPT from meteorological to hydrological drought in the PRB. Key Points: Pearl River Basin (PRB) was classified into five subregions with similar dry and wet characteristics using K‐means cluster analysis method Hydrological drought was more serious than meteorological drought in the PRB, and the drought propagation times (DPTs) were 2–6 months Large‐scale climate patterns (El‐Niño Southern Oscillation and Pacific Decadal Oscillation) are important factors that affect the DPT from meteorological to hydrological drought in the PRB